Sprachliches Rollenverhalten: korpuspragmatische Studien zu divergenten Kontextualisierungen in Mündlichkeit und Schriftlichkeit - Müller, Marcus (Sprache und Wissen, 2015)
This corpus pragmatic study addresses the symptomatic function of lexical and grammatical constructions in relation to the speaker's affiliation with groups that develop discourses through their shared social position. It uses a corpus of spoken and written communications on the bioethics debate to examine qualitative and quantitative correlations between spoken and written verbal patterns and roles, medium and context --
Literaturverz. S. [331] - 353
Keywords: Hochschulschrift; Diskursanalyse; Korpus; Textlinguistik; Gesprochene Sprache; Sprachhandeln; Soziale Rolle; Deutsch